Pendampingan Kegiatan Ramadhan Bertadarus bagi Jamaah Cilik di Masjid Darul Rahman Palangka Raya - A'ini, Nova Nur; Majidi, Muhammad Wahid (Lembaga Yasin AlSys, 2025)
Ramadhan is a significant moment for Muslims to enhance religious practices, including tadarus (recitation) of the Qur’an. Masjid Darul Rahman Palangka Raya organized a tadarus mentoring program for young congregants as an effort to instill love for the Qur’an from an early age. The aim of this initiative is to improve children’s Qur’anic reading skills and instill spiritual values during the month of Ramadhan. The method used is service learning, implemented through three stages: pre-implementation (needs assessment and goal formulation), implementation (mentoring sessions), and post-implementation (evaluation and reflection). The results show an improvement in participants’ Qur’an reading ability and high enthusiasm among children in participating in the program. Additionally, a religious, enjoyable, and character-building learning environment was established. This program has the potential to serve as a model for mosque-based early childhood religious education that can be implemented sustainably.